Desafios estéticos da imersividade no documentário interactivo - Ana Catarina Gomes Monteiro (2016)
This work proposes a taxonomical study of immersiveness in interactive documentary. The objective is to show the interactive documentary as a genre evolving and as a set of representations that are part of a process of transformation and technological change. It studies the characteristics that compose the interactive documentary, the medium in which it propagates, the differences in the representation of perspective of reality, bringing new meanings and new forms of presentation. Discusses the new relationships that arises from the interaction between authors and users, and how this changes the roles assigned to each of them. Proposes glimpse the aesthetic challenges of immersiveness in the interactive documentary that influence how we see and understand what is represented, and the transformative power that this genre has on the audience. Keywords: documentary, interactive, immersiveness, digital environments, audience